The complete mitochondrial genome sequence of Eimeria magna (Apicomplexa: Coccidia). (3rd September 2015) - Tian, Si-Qin; Cui, Ping; Fang, Su-Fang; Liu, Guo-Hua; Wang, Chun-Ren; Zhu, Xing-Quan
Abstract: In the present study, we determined the complete mitochondrial DNA (mtDNA) sequence of Eimeria magna from rabbits for the first time, and compared its gene contents and genome organizations with that of seven Eimeria spp. from domestic chickens. The size of the complete mt genome sequence of E. magna is 6249 bp, which consists of 3 protein-coding genes ( cyt b, cox 1 and cox 3), 12 gene fragments for the large subunit (LSU) rRNA, and 7 gene fragments for the small subunit (SSU) rRNA, without transfer RNA genes, in accordance with that of Eimeria spp. from chickens. The putative direction of translation for three genes ( cyt b, cox 1 and cox 3) was the same as those of Eimeria species from domestic chickens. The content of A + T is 65.16% for E. magna mt genome (29.73% A, 35.43% T, 17.09 G and 17.75% C). The E. magna mt genome sequence provides novel mtDNA markers for studying the molecular epidemiology and population genetics of Eimeria spp. and has implications for the molecular diagnosis and control of rabbit coccidiosis.